The Role of Product Design and Liberation in the Optimisation of Recycling Passenger Vehicles (8f1bd552-2690-4dde-a673-5d56b48b0787) - Antoinette van Schaik; Markus A. Reuter; Bernardete Castro; Han Remmerswaal (International Mineral Processing Congress, 2003)
This paper describes the inseparable relation between product design, liberation, and metallurgical recovery in the optimisation of the recycling of passenger vehicles. This is illustrated by the use of an optimisation model that uses among others a material combination matrix based on metallurgical process data, which depicts the consequences of the quality of intermediate recycling products on the metallurgical material recovery and final alloy metal quality. Various simulations will illustrate the effect of changes in product design and hence liberation on the recycling of end-of-life vehicles. Although this paper focuses on cars, the discussion is equally valid for any end-of-life product. Calibration of the model will be discussed with reference to experiments carried out in order to study the optimal recovery of aluminium applications used in passenger vehicles.